Conversion factors and general equations applied in agricultural and forest meteorology (Agrometeoros, 2020)
Scientific communication in agricultural and forest meteorology requires a correct conversion of units and the adequate use of equations. In general, most of conversion and equations are found separately in a specific book, paper or document. Thus, here we propose a single document with conversion units of solar radiation, evapotranspiration, resource use efficiency, carbon balance, ecophysiology, trace gases and water; and general equations: Penman-Monteith, canopy conductance, decoupling factor and Bowen ratio. This document has a lot of value for teaching, for scientists and as a quick reference.